Profil Pelajar Pancasila: Studi Kearifan Lokal “Ecoprint” Melalui Project Base Learning - Ibermarza (Idarotuna : Journal of Administrative Science, 2023)
This research is a study implementing the profil pelajar pancasila based on project-based learning by exploring a local wisdom "Ecoprint" at MI Raudhatul Ma'arif, Bungo Regency. This research stems from the lack of insight of students in implementing Pancasila values in everyday life; the independent curriculum has not been implemented through a project-based learning model. Apart from that, the learning strategies used are still not effective for project-based learning. The model used in this research is the Kemmis and Taggart model through data collection techniques using observation, interview, and documentation techniques, which aim to obtain data on student learning outcomes. Based on the research results, this activity resulted in an increase in the very good category. Meanwhile, student activity also increased by 92%, with 90 students showing the five dimensions of the profil pelajar pancasila. This study contributes to the profil pelajar pancasila paradigm based on project-based learning, especially on the theme of local wisdom